Serum Copper and Zinc in a Representative Sample of Bulgarian Population - Ivanova I. (Sciendo, 2016)
Copper (Cu) and zinc (Zn) are essential for life. Body Cu and Zn content depends on variety of factors - age, gender, and diet, type of drinking water, geographical location and genetic predisposition. Copper status becomes even more relevant not only in rare genetic disorders such as Wilson disease but in diseases such as cardiovascular ones, impaired glucose tolerance and neuro-degenerative and tumor diseases. The study aimed to examine the distribution of serum Cu and Zn in a representative group of the Bulgarian population and to describe factors which influence metal content. It also aimed to describe the link between serum Cu levels and the frequency of Alzheimer’s disease (AD) in Bulgarians. Cu and Zn in serum were measured in 379 individuals (172 males and 207 females) from 5 different regions in Bulgaria by flame atomic absorption using AAnalyst 400, Perkin Elmer. Statistical analyses were performed by SPSS, 19. Median and inert-quartile range (IQR) for blood Cu were 15.89 (13.87-7.89) μmol/L and for Zn - 13.00 (11.7-14.68) μmol/L in the examined group. Higher Cu levels in females than in males were found (p < 0.001). Decrease of Zn with aging was established (p > 0.05). Significant difference (p < 0.05) was found in serum Cu between young people (< 30 year old) and adults over 61 year old. Statistically significant difference in Cu and Zn was observed (p < 0.05) in respect of residences. Difference without significance was measured between serum lipids and serum Cu (p = 0.541) and Zn (p = 0.741).